Change in minimum indexed left atrial volume predicts incident heart failure: the multi-ethnic study of atherosclerosis. (25th January 2023) - Lim, D; Varadarajan, V; Quinaglia, T; Pezel, T; Wu, C; Noda, C; Heckbert, S; Bluemke, D; Ambale-Venkatesh, B; Lima, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background and Purpose: Longitudinal change in the left atrium prior to the onset of heart failure has not been as well studied as left atrial (LA) dysfunction in pre-existing heart failure. This study used cardiac magnetic resonance (CMR) imaging to investigate the relationship between longitudinal change in LA volume and function and incident heart failure (HF), in a multi-ethnic population free of known cardiovascular disease at baseline. Methods and Results: In the Multi-Ethnic Study of Atherosclerosis (MESA), 2470 participants (60±9 years, 47% males), free at baseline of clinically recognized cardiovascular disease, had LA volume, emptying fractions and peak longitudinal strain assessed with Multimodality Tissue Tracking (MTT; version 6.0 Toshiba, Japan) on CMR imaging at baseline (2000-02) and at follow-up 9.4±0.6 years later. Seventy three (3%) participants subsequently developed incident HF 7.1±2.1 years after the follow-up CMR exam. In cox regression models, an annualized change in all LA parameters were significantly associated with an increased risk of incident HF. An annual increase of 1ml/m2 in minimum indexed LA volumes (∆LAVimin) was most strongly associated with the risk of incident HF (Hazard Ratio(HR)=1.85, 95% confidence interval(CI) [1.49-2.29], P<0.001) and improved model reclassification and discrimination in predicting incident HF (c-statistic=0.80, 95%CI [0.75-0.86]; NRI=0.13, P=0.04; IDI=0.04, P=0.01; x2=6.52, P=0.69) adjusting for known risk factors (age, gender, systolic blood pressure, anti-hypertensive medication use, smoking status, diabetes mellitus, total cholesterol, previous atrial fibrillation) and baseline LA parameters. Conclusion: In this multi-ethnic population free of clinical cardiovascular disease at baseline, ∆LAVimin was most strongly associated with, and incrementally predictive of incident HF, after adjusting for known risk factors and baseline LA measures.